Selenium nanoparticles based on Amphipterygium glaucum extract with antibacterial, antioxidant, and plant biostimulant properties - Jorge J. O. Garza-García; José A. Hernández-Díaz; Janet M. León-Morales; Gilberto Velázquez-Juárez; Adalberto Zamudio-Ojeda; Jenny Arratia-Quijada; Oscar K. Reyes-Maldonado; Julio C. López-Velázquez; Soledad García-Morales (Journal of Nanobiotechnology, 2023)
Abstract Background In recent years, crop production has expanded due to the variety of commercially available species. This increase in production has led to global competition and the search for biostimulant products that improve crop quality and yield. At the same time, agricultural products that protect against diseases caused by phytopathogenic microorganisms are needed. Thus, the green synthesis of selenium nanoparticles (SeNPs) is a proposal for achieving these needs. In this research, SeNPs were synthesized from methanolic extract of Amphipterygium glaucum leaves, and chemically and biologically characterized. Results The characterization of SeNPs was conducted by ultraviolet–visible spectrophotometry (UV–Vis), scanning electron microscopy (SEM), electron microscopy transmission (TEM), Dynamic Light Scattering (DLS), energy dispersion X-ray spectroscopy (EDX), and infrared spectrophotometry (FTIR) techniques. SeNPs with an average size of 40–60 nm and spherical and needle-shaped morphologies were obtained. The antibacterial activity of SeNPs against Serratia marcescens, Enterobacter cloacae, and Alcaligenes faecalis was evaluated. The results indicate that the methanolic extracts of A. glaucum and SeNPs presented a high antioxidant activity. The biostimulant effect of SeNPs (10, 20, 50, and 100 µM) was evaluated in vinca (Catharanthus roseus), and calendula (Calendula officinalis) plants under greenhouse conditions, and they improved growth parameters such as the height, the fresh and dry weight of roots, stems, and leaves; and the number of flowers of vinca and calendula. Conclusions The antibacterial, antioxidant, and biostimulant properties of SeNPs synthesized from A. glaucum extract demonstrated in this study support their use as a promising tool in crop production. Graphical Abstract